Movement and Distribution of Cryptolestes ferrugineus (Coleoptera: Laemophloeidae) Adults Under Different Temperature Differences in Different Lengths of Horizontal Grain Columns. Issue 3 (28th June 2022) - Anukiruthika, T; Jayas, Digvir S; Jian, Fuji
Abstract: Understanding insect movement and distribution is critical for developing an effective insect pest management protocol. Movement and distribution of adult Cryptolestes ferrugineus (Stephens) in response to nominal temperature differences of 5, 10, 15, and 20°C in 1- and 2-m horizontal columns filled with 12.5% moisture content wheat were studied in 24, 48, and 72 h of movement times. In the wheat columns without temperature differences, adults had a diffusion distribution pattern caused by their random movement. Adults showed bias movement to the warmer grain in wheat columns with temperature differences and preferred the warmer grain regardless of the magnitude of temperature differences in less than 24 h. Their distribution did not have significant differences among different movement times in 1- or 2-m columns. About 40% of adults moved to the warmer wheat located at 0.4 to 0.5 m in the 1 m column but did not move to the warmer wheat located at 0.9 to 1 m in the 2-m column. Therefore, length of grain column influenced detection of warmer grain by insects. Adults under different temperatures had a similar response as that under linear temperature gradients.